2020
DOI: 10.5194/soil-6-115-2020
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of soil carbon and aggregation after strong warming of a subarctic Andosol under forest and grassland cover

Abstract: Abstract. The net loss of soil organic carbon (SOC) from terrestrial ecosystems is a likely consequence of global warming and may affect key soil functions. The strongest changes in temperature are expected to occur at high northern latitudes, with forest and tundra as prevailing land cover types. However, specific soil responses to warming in different ecosystems are currently understudied. In this study, we used a natural geothermal soil warming gradient (0–17.5 ∘C warming intensity) in an Icelandic spruce f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 67 publications
(72 reference statements)
2
15
2
Order By: Relevance
“…Studies with a relatively long time span of observation (e.g. Poeplau et al, 2020, Melillo et al, 2002, 2017) reported results that are consistent with our findings. Melillo et al (2017) observed a long‐term pattern of rapid SOC loss at the start of soil warming but reaching a new equilibrium between SOC mineralization and build‐up later in the experiment.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Studies with a relatively long time span of observation (e.g. Poeplau et al, 2020, Melillo et al, 2002, 2017) reported results that are consistent with our findings. Melillo et al (2017) observed a long‐term pattern of rapid SOC loss at the start of soil warming but reaching a new equilibrium between SOC mineralization and build‐up later in the experiment.…”
Section: Discussionsupporting
confidence: 93%
“…that in the S+A, S+C and rSOC fractions) was the same in all soils along the warming gradient. This is in contrast to the findings reported in a similar geothermal warming experiment in Iceland, where SOC in the S+A fraction, as well as aggregates, declined strongly with warming; in this study, the silt and clay-associated SOC was lost at a similar rate as bulk SOC (Poeplau et al, 2016(Poeplau et al, , 2020. However, this does not imply that those fractions were not affected by warming in the present study.…”
Section: Response Of Different Soil Organic Matter Fractionscontrasting
confidence: 99%
See 3 more Smart Citations